The economic burden experienced by carers of children who had a critical deterioration at a tertiary children's hospital in the United Kingdom (the DETECT study): an online survey - Eduardo Costa; Céu Mateus; Bernie Carter; Sarah Siner; Dawn Jones; Leah Evans; Jenny Preston; Fulya Mehta; Caroline Lambert; Bruce Hollingsworth; Enitan D. Carrol; Gerri Sefton (BMC, 2023)
Abstract Background Unplanned critical care admissions following in-hospital deterioration in children are expected to impose a significant burden for carers across a number of dimensions. One dimension relates to the financial and economic impact associated with the admission, from both direct out-of-pocket expenditures, as well as indirect costs, reflecting productivity losses. A robust assessment of these costs is key to understand the wider impact of interventions aiming to reduce in-patient deterioration. This work aims to determine the economic burden imposed on carers caring for hospitalised children that experience critical deterioration events. Methods Descriptive study with quantitative approach. Carers responded to an online survey between July 2020 and April 2021. The survey was developed by the research team and piloted before use. The sample comprised 71 carers of children admitted to a critical care unit following in-patient deterioration, at a tertiary children's hospital in the UK. The survey provides a characterisation of the carer's household and estimates of direct non-medical costs grouped in five different expenditure categories. Productivity losses can also be estimated based on the reported information. Results Most carers reported expenditures associated to the child's admission in the week preceding the survey completion. Two-thirds of working carers had missed at least one workday in the week prior to the survey completion. Moreover, eight in ten carers reported having had to travel from home to the hospital at least once a week. These expenditures, on average, amount to £164 per week, grouped in five categories (38% each to travelling costs and to food and drink costs, with accommodation, childcare, and parking representing 12%, 7% and 5%, respectively). Additionally, weekly productivity losses for working carers are estimated at £195. Conclusion Unplanned critical care admissions for children impose a substantial financial burden for carers. Moreover, productivity losses imply a subsequent cost to society. Even though subsidised hospital parking and on-site accommodation at the hospital contribute to minimising such expenditure, the overall impact for carers remains high. Interventions aiming at reducing emergency critical care admissions, or their length, can be crucial to further contribute to the reduction of this burden. Trial Registration Current Controlled Trials ISRCTN61279068, date of registration 07/06/2019, retrospectively registered.